Prevalence of Lower Third Molar Angulations in Duhok Province of Kurdistan Region- Iraq - Ahmed Ali Mohammed; EVAN NAMRUD YOUHANNA; Sargon Shazo; SANDY ANDRAWS HANA (University of Mosul, College of Dentistry, 2024)
Aims: The current retrospective radio-graphical study aimed to find the prevalence of lower third molar impactions and angulations in a sample population of Duhok Province -Kurdistan region, Iraq. Materials and Methods: The study included randomly chosen Orthopantomograms (OPGs) of 1316 adults; "682 males and 634 females" with ages ranging between (21 - 50 years) old who were referred to the College of Dentistry / Oral and Maxillofacial Surgery Department / University of Duhok between the years (2020 and 2023). A total of 502 OPGs were included in the study with impacted lower wisdom teeth (344 bi-lateral impactions, 158 uni-lateral impactions), Analysis was made according to the classifications of Pell and Gregory and Winter's categories of radiographic images (OPGs) to determine the prevalence and angulations of impacted lower wisdom teeth. Results: The data was collected from 502 patients "183 males and 319 females" OPGs, with a total of (846) impacted lower wisdom teeth (344 bi-lateral impactions, 158 uni-lateral impactions). The prevalence of mesioangular impactions was 28.2% being the most common. Vertical angulations were significantly lower than other impactions 3.7%. There was a significant difference between female and male-impacted third molars "18.8% in females and 10.4% in males" (577 teeth in females and 269 teeth in males). Conclusion: Mesioangular lower wisdom teeth impactions were recorded to be the most common type found with females being more than in males.